History and Philosophy of Jewish Education: A Bibliographical Essay - Frizzell, Lawrence E (Journal of Dharma, 1984)
Study and learning are integral to the Jewish way of life. The search for knowledge is rooted first in the experience of God as teacher and the appreciation of the treasure bequeathed in his Word. Thus, any review of the Jewish culture points to the relationship between the people and the Bible, its commentaries and numerous works deriving from the spirituality it offers.